Private Alternatives and Early Retirement Programs - Matias Eklöf; Daniel Hallberg (Uppsala University, Department of Economics, 2004)
This paper describes early retirement option programs in collective agreements in Sweden during the 1990s. We highlight the differences between actual pension benefits and those stipulated in the standard agreements. We find that the individuals frequently face far better options than those given by standard agreements. The mix and the timing of pensions is usually done in a non-trivial way. Thus, if we just relied on the standard agreement text, one important implication of these findings is that the effects of economic incentives on retirement very well might be over-estimated.
urn:nbn:se:uu:diva-4512
Keywords: J14; J21; 330; Retirement; early retirement programs; occupational pension; Altersgrenze; Arbeitszeitgestaltung; Individualismus; Schweden